Shoes Sales Forecasting Using Autoregressive Integrated Moving Average (arima) (case Study UD.Wardana Mojokerto) - Achmad Kiki Qushayri Wahyu Kusuma; Eko Prasetyo; Rifki Fahrial Zainal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Shoes sales is increase of day by day along with growing trend in the society. This makes shoemanufacturers demand to fulfill the customer needs. UD. Ward as one of the shoe manufacturers in Mojokertocity trying to fulfill the customer needs efficiently in order that the make sales fit with production. To predictsales of shoes used Autoregressive Integrated Moving Average (ARIMA) method. ARIMA forecasting method isone of methods that According to historical data. Before go into the forecasting stage, differentiated the salesdata per day during the year 2015-2016 ACF and PACF formula used Whose function is to Determine the valueof p and q coefficient of the which will later be used in forecasting models in every formula that is AR , MA andARMA. Result of this research shows that for the marching band category Obtained the best models that is MAwith forecasting the result at the last period of 95.6432 and MSE of 472.4514. Obtained fashion category for thebest models of forecasting that is AR with the result at the last period of 57.1872 and MSE of 304.8306. Obtainedcategory for the best wedding that is AR models with forecasting the result at the last period of 21.4206 and MSEof 118.0681.